KARAKTERISTIK PERILAKU PERJALANAN RUMAH TANGGA PENGGUNA SEPEDA MOTOR DI PINGGIRAN KOTA SEMARANG - Manullang, Okto Risdianto; Tamin, Ofyar Z.; Syabri, Ibnu; Sjafruddin, Ade (Prosiding Forum Studi Transportasi Antar Perguruan Tinggi, 2015)
With urban sprawl, public transport often fails to accommodate the high travel demand; population is increasingly spread out while most activities stay in the city centers. This creates variations in travel behavior, affected by the traveler himself and his location. This study examines household travel behavior characteristic using motorcycle in Semarang City fringes quantitatively using crosstab analysis. Analysis results showed that distance to working location has the biggest influence in the husband and wife travel behavior on weekday, as the main actor of household production and consumption which play a main role in the decisions being made in the household. On the other hand, the frequency of trips on the weekend is influenced by a number of members of the family and household income, as well as travel time is affected by household income. This suggests that the characteristics of household travel behavior motorcyclists on weekends is more influenced by household income. Typically these households undertake recreational walks.